The contribution of matrix metalloproteinases and their inhibitors to the development, progression, and rupture of abdominal aortic aneurysms - Atkinson, Georgia; Bianco, Rosaria; Di Gregoli, Karina; Johnson, Jason L. (Frontiers in Cardiovascular Medicine, 2023)
Abdominal aortic aneurysms (AAAs) account for up to 8% of deaths in men aged 65 years and over and 2.2% of women. Patients with AAAs often have atherosclerosis, and intimal atherosclerosis is generally present in AAAs. Accordingly, AAAs are considered a form of atherosclerosis and are frequently referred to as atherosclerotic aneurysms. Pathological observations advocate inflammatory cell infiltration alongside adverse extracellular matrix degradation as key contributing factors to the formation of human atherosclerotic AAAs. Therefore, macrophage production of proteolytic enzymes is deemed responsible for the damaging loss of ECM proteins, especially elastin and fibrillar collagens, which characterise AAA progression and rupture. Matrix metalloproteinases (MMPs) and their regulation by tissue inhibitors metalloproteinases (TIMPs) can orchestrate not only ECM remodelling, but also moderate the proliferation, migration, and apoptosis of resident aortic cells, alongside the recruitment and subsequent behaviour of inflammatory cells. Accordingly, MMPs are thought to play a central regulatory role in the development, progression, and eventual rupture of abdominal aortic aneurysms (AAAs). Together, clinical and animal studies have shed light on the complex and often diverse effects MMPs and TIMPs impart during the development of AAAs. This dichotomy is underlined from evidence utilising broad-spectrum MMP inhibition in animal models and clinical trials which have failed to provide consistent protection from AAA progression, although more encouraging results have been observed through deployment of selective inhibitors. This review provides a summary of the supporting evidence connecting the contribution of individual MMPs to AAA development, progression, and eventual rupture. Topics discussed include structural, functional, and cell-specific diversity of MMP members; evidence from animal models of AAA and comparisons with findings in humans; the dual role of MMPs and the requirement to selectively target individual MMPs; and the advances in identifying aberrant MMP activity. As evidenced, our developing understanding of the multifaceted roles individual MMPs perform during the progression and rupture of AAAs, should motivate clinical trials assessing the therapeutic potential of selective MMP inhibitors, which could restrict AAA-related morbidity and mortality worldwide.